Control Oriented Aerodynamic Design Optimization for an Aerial Manipulator - Γαβρίδης, Γεώργιος Χ. (Σχολή Μηχανολόγων Μηχανικών, 2014)
Historically, aerial vehicles with more than two rotors have not been very commonly used, primarily because most of the preferable payloads could be lifted by using only one or two rotors. However, these aerial vehicles possess several characteristics which make them attractive. Naturally, the rst one is the superior payload capacity and the second is the simplicity of the necessary control system. In fact, the control of such a vehicle can be achieved by independently tuning the speed (rpm) of each rotor. This control system is particularly suitable for small UAVs, because it reduces the mechanical complexity of the rotors reducing in that way the volume and the weight of the body- structure respectively. Therefore, taking the above into consideration, still remains challenging to structure a completely new aerial vehicle that will be classi ed also in rotary-wing VTOL air crafts. This air craft will be called Aerial Manipulator and could be considered as a small UAV that interacts with the environment via an end-e ector by applying actuating force and torque. As this is an aerial vehicle, it is essential to have a complete understanding of the rotary-wing VTOL ight principles that will be applied partially in this analysis. This Diploma thesis presents a detailed Static Design Model of this new UAV that will de ne the optimal number of rotors, their locations as well as their directions on the body structure, with respect to the design limitations. These locations and directions are products of several optimization problems with general goal the low body volume, for which solving methodology is proposed. In addition to that, with the aim of introducing possible aerodynamic interaction between the rotors appropriate experimental results were considered. Moreover, a search was made on the market so as to select appropriate ying components such as propellers and motors that will match the Design requirements. To conclude, the overall mathematical equations implied from the Static Design problem accompanied by the characteristics and the limitations incorporated from the commercial components, were programmed in Matlab environment. In this manner, can be found the maximum actuating force and torque the Aerial Manipulator can apply via the end-e ector